PENGGLASIRAN BENDA KERAMIK: PENERAPAN SELF-DETERMINED LEARNING - Sulistya, Rohmat (Jurnal Pendidikan Seni dan Industri Kreatif, 2022)
ABSTRACT Ceramics glazing is a unique subject because this subject contains both of art and science that are quite deep. Aspects of art are related to ceramic art, while science is related to chemistry, mathematics, and physics. This learning material is quite complex and requires a lot of effort to master. In the curriculum (K13 and Kurikulum Merdeka), this material is studied as a minor competence to support the major competence of Pembentukan Keramik. As a result, teachers' mastery in glazing and how it’s been tought face limitations. While in industry, glazing is an important determinant of final ceramic products. The development of ceramic products is currently more determined by the quality of the glaze rather than its shape. This study aims to describe aspects related to ceramic glazing learning and to propose a logical learning method so that this material is mastered well. The results of the study show that the position of this material in the curriculum is not strong enough to be studied comprehensively while this material contains the fundamentals of glaze theory that must be studied properly and intact. Limited training opportunities for teachers and the duration of the training make self-determined learning as a logical choice to systematically learn this subject. The success keys of this learning approach are mindset change in self-studying, use of reliable learning management system, and increasing self-motivation to study. Keywords: glazing, ceramic, self-determined learning. ABSTRAK Materi pengglasiran benda keramik adalah materi yang unik karena pada materi ini termuat aspek seni dan sains yang cukup dalam. Aspek seni berkaitan dengan seni kriya keramik, sedangkan sains berkaitan dengan kimia, matematika, dan fisika. Materi ini cukup kompleks dan memerlukan usaha keras untuk menguasainya. Di dalam kurikulum (K13 dan Kurikulum Merdeka), materi ini dipelajari sebagai kompetensi minor untuk mendukung kompetensi mayor Pembentukan Keramik. Akibatnya, penguasaan guru akan materi pengglasiran yang kompleks dan usaha pembelajarannya menghadapi keterbatasan. Sementara di dunia industri, pengglasiran adalah penentu penting pada produk akhir keramik. Pengembangan produk keramik saat ini lebih ditentukan oleh kualitas pengglasiran daripada bentuk benda. Kajian ini bertujuan untuk mendeskripsikan aspek-aspek yang terkait dengan pembelajaran materi pengglasiran benda keramik dan menggagas metode pembelajaran yang logis agar materi ini dikuasai dengan baik. Hasil kajian menunjukkan posisi materi ini pada kurikulum kurang cukup kuat untuk dipelajari secara komprehensif, padahal materi ini memuat fundamen teori glasir yang harus dipelajari dengan baik dan utuh. Dengan keterbatasan kesempatan diklat bagi guru dan durasi diklat, self-detemined learning dapat menjadi pilihan logis untuk menguasai materi ini secara sistematis. Perubahan mindset untuk belajar mandiri, dukungan learning management system, dan penumbuhan motivasi diri untuk belajar menjadi kunci keberhasilan pendekatan pembelajaran ini. Kata kunci: pengglasiran, benda keramik, self-determined learning